Pause sites promote transcriptional termination of mammalian RNA polymerase II. - Gromak, N; West, S; Proudfoot, N (2006)
Polymerase II (Pol II) transcriptional termination depends on two independent genetic elements: poly(A) signals and downstream terminator sequences. The latter may either promote cotranscriptional RNA cleavage or pause elongating Pol II. We demonstrate that the previously characterized MAZ4 pause element promotes Pol II termination downstream of a poly(A) signal, dependent on both the proximity of the pause site and poly(A) signal and the strength of the poly(A) signal. The 5'-->3' exonuclease Xrn2 facilitates this pause-dependent termination by degrading the 3' product of poly(A) site cleavage. The human beta-actin gene also possesses poly(A) site proximal pause sequences, which like MAZ4 are G rich and promote transcriptional termination. Xrn2 depletion causes an increase in both steady-state RNA and Pol II levels downstream of the beta-actin poly(A) site. Taken together, we provide new insights into the mechanism of pause site-mediated termination and establish a general role for the 5'-->3' exonuclease Xrn2 in Pol II termination.